Outcomes in children under 12 months of age undergoing adenotonsillectomy for sleep‐disordered breathing. (2nd July 2013) - Cheng, Jeffrey; Elden, Lisa
Abstract : Objectives/Hypothesis: To evaluate the incidence, safety, and efficacy of adenotonsillectomy for the treatment of sleep‐disordered breathing (SDB) or obstructive sleep apnea (OSA) in infants 12 months of age and younger. Study Design: Case series study. Methods: A retrospective review was performed of pediatric patients, 12 months of age or younger, who underwent adenotonsillectomy between January 1, 2006 and May 18, 2012 at a tertiary‐care children's hospital. Results: Only 25 patients were identified. Most of the patients were male, with an average age of 10.6 months. All of the patients were admitted to the pediatric intensive care unit (PICU) postoperatively. The average length of stay was 2.7 days (range, 1–9 days). Twelve patients were otherwise healthy infants, whereas 13 had significant comorbid conditions. Adenotonsillectomy was successful in treating OSA/SDB in all of the otherwise healthy patients and less effective in patients who had comorbid conditions (38.5%) ( P = .002). Postoperative complications occurred in three of the 12 otherwise healthy patients, and in four of the 13 patients with comorbid conditions. Conclusions: Adenotonsillectomy in infants under 12 months old is uncommonly performed, but is more effective in treating OSA/SDB in patients who are healthy than in those with comorbid conditions. Postoperative PICU monitoring is recommended given that the risks of postoperative complications in this young age group is high (28%) and often related to perioperative oxygen requirements. Patients should also be counseled about the potential for symptomatic adenoid regrowth, for which revision adenoidectomy may be indicated. Level of Evidence: 4. Laryngoscope, 123:2281–2284, 2013